Gonadotropin Inhibitory Hormone and Its Receptor: Potential Key to the Integration and Coordination of Metabolic Status and Reproduction - Bédécarrats, Grégoy Y.; Hanlon, Charlene; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2022)
Since its discovery as a novel gonadotropin inhibitory peptide in 2000, the central and peripheral roles played by gonadotropin-inhibiting hormone (GnIH) have been significantly expanded. This is highlighted by the wide distribution of its receptor (GnIH-R) within the brain and throughout multiple peripheral organs and tissues. Furthermore, as GnIH is part of the wider RF-amide peptides family, many orthologues have been characterized across vertebrate species, and due to the promiscuity between ligands and receptors within this family, confusion over the nomenclature and function has arisen. In this review, we intend to first clarify the nomenclature, prevalence, and distribution of the GnIH-Rs, and by reviewing specific localization and ligand availability, we propose an integrative role for GnIH in the coordination of reproductive and metabolic processes. Specifically, we propose that GnIH participates in the central regulation of feed intake while modulating the impact of thyroid hormones and the stress axis to allow active reproduction to proceed depending on the availability of resources. Furthermore, beyond the central nervous system, we also propose a peripheral role for GnIH in the control of glucose and lipid metabolism at the level of the liver, pancreas, and adipose tissue. Taken together, evidence from the literature strongly suggests that, in fact, the inhibitory effect of GnIH on the reproductive axis is based on the integration of environmental cues and internal metabolic status.